Mechanism of Qilong Capsule against Myocardial Ischemia-Reperfusion Injury Based on Network Pharmacology and Experimental Validation - Li, Lingxu; Ye, Jingxue; Zhou, Jiahui; Wang, Zhihui; Li, Ruoyun; Wang, Min; Sun, Guibo (Combinatorial Chemistry & High Throughput Screening, 2025)
IntroductionQilong capsule (QC) has been used clinically to treat ischemic stroke in China. This study evaluated the therapeutic effects of QC on myocardial ischemia-reperfusion injury (MIRI) and its potential mechanisms.MethodsThe components and candidate targets of QC against MIRI were predicted by network pharmacology via relevant databases such as TCMSP, BATMAN-TCM, GeneCards. The potential mechanisms were predicted by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses and verified by enzyme-linked immunosorbent assay (ELISA) and Western blot.ResultsNetwork pharmacology analysis indicated that the cardioprotective effect of QC against MIRI was associated with inflammatory pathways. We further confirmed that QC effectively decreased the levels of inflammatory factors, including hs-CRP and MCP-1, and suppressed the expression of TNF-α and the phosphorylation of STAT3.ConclusionThis study provides evidence for further clinical applications of QC for MIRI therapy.
Keywords: STAT3